Factors influence employee level of integrity in automotive company / Norziana Lokman and Nur Maisarah Mahadzir - Lokman, Norziana; Mahadzir, Nur Maisarah (Faculty of Business and Management, Universiti Teknologi MARA, Shah Alam, Malaysia, 2019)
This study investigated the factors that influence employee level of integrity at UMW Toyota Motor. There are three factors identified as the predictor in the study, namely, individual, organizational, and situational factors, which are expected to affect employee level of integrity. Data were collected through questionnaires distributed between October 2018 and March 2019 to all employees of UMW Toyota Motor. A total of 300 respondents were approached, and 137 (46%) questionnaires were returned for analysis. The data collected were analyzed using descriptive, correlation, and regression analysis. The finding concluded that the level of integrity among employees of UMW Toyota Motor is high. The regression analysis result showed that situational factors have significant and positively associated with the employee level of integrity. The result indicated that situational factors such as peer pressure, financial distress, leadership influence, and ethical norms at the workplace affected the integrity level of employees.